Potential Usage of Rice Husk Ash-Cement Based Soil in Subbase and Base Courses in Road Construction - Phan, Vu To-Anh; Nguyen, Van-Long; Tran, Huu-Bang; Le, Van-Bach (International Journal of Integrated Engineering, 2023)
This paper presents an experimental study of rice husk ash-cement-based soil for layers in roadway construction. Rice husk ash (RHA) used in this study is a by-product of rice milling. In this work, twelve proportion mixes were used in this work with varying quantities of RHA (0-30%) and Portland cement blended amounts of 4, 6, 8%. The specimens were prepared by the Proctor mould method, conditioned at room temperature, and tested in soaked and unsoaked conditions. Specified curing periods of 7, 14, 28 days were applied for all types of specimens. Some engineering tests were carried out such as proctor compaction, unconfined compressive strength, splitting tensile strength, and the stiffness of stabilized soil. Test results indicated a general decrease in the maximum dry density (MDD) and increased optimum moisture content (OMC) with an increase in RHA content. Adding cement and RHA significantly improved the geotechnical properties of stabilized soils, including compressive strength, splitting tensile strength, elastic modulus. In addition, the combination of 80% soil and 20% RHA and 6% cement can be used as the optimum proportion which satisfied the grade 3 of soils stabilized with inorganic adhesive substances, chemical agents, or reinforced soil for road construction, as indicated in the current Vietnamese standard.